Pengaruh Work Family Conflict Dan Financial Compensation Terhadap Employee Performance di CV Panji Roster Dengan Social Support Sebagai Variabel Moderasi - Elan Suryonoo; Indah Rahayu (LPPM Universitas An Nuur, 2026)
Background: Competent and qualified human resources play a crucial role in supporting organizational success, as their skills, knowledge, and work ethic enable them to adapt to dynamic business changes. Employee performance is a strategic factor determining competitiveness and the achievement of organizational goals, both short-term and long-term. This also applies to CV Panji Roster, whose success is highly dependent on the optimal performance of its employees. Purpose: The purpose of this study is to describe and analyze the influence of financial compensation, work-family conflict, and employee performance, as well as the role of social support as a moderating variable on CV Panji Roster employees. Method: This study employed quantitative methods. The sample used in this study was 65 respondents, using probability sampling and total sampling techniques. Data analysis used Smart Partial Least Squares (PLS) version 3.0. Conclusion: It can be concluded that financial compensation can help reduce the pressure that triggers work-family conflict and can improve employee performance, while work-family conflict can reduce employee performance, and social support plays a role in moderating or weakening the influence of work-family conflict on employee performance. Suggestion: This study removed three indicators that did not meet the criteria: one indicator for social support, one indicator for work-family conflict, and one indicator for financial compensation. These indicators can be replaced with ones that better align with the company's criteria. Furthermore, this study also noted the potential for other variables, such as work motivation, rewards, work environment, and organizational culture, to drive improved employee performance. Therefore, it is recommended that these be considered in future research as supporting factors in addressing workplace conflict. Keywords: Work-Family Conflict, Financial Compensation, Social Support, Employee Performance.